Adaptive Multi-Switching Synchronization of High-Order Memristor-Based Hyperchaotic System with Unknown Parameters and Its Application in Secure Communication. (19th December 2019) - Xiong, Zhili; Qu, Shaocheng; Luo, Jing
Abstract : This article investigates an adaptive multi-switching synchronization for two identical high-order memristor-based hyperchaotic systems with uncertain parameters. Firstly, the dynamic characteristics of two high-order memristor hyperchaotic systems with uncertain parameters are analyzed. Then, an adaptive multi-switching controller is designed to realize the multi-switching synchronization of the two high-order hyperchaotic systems, and the unknown parameters of the systems are identified to their true values. Furthermore, numerical simulation results testify the effectiveness of the proposed strategy. Finally, the proposed algorithm applied in secure communication of masking encryption and image encryption is validated by statistical analysis.